2021
DOI: 10.3390/medicina57040308
|View full text |Cite
|
Sign up to set email alerts
|

Sports Activity and Arrhythmic Risk in Cardiomyopathies and Channelopathies: A Critical Review of European Guidelines on Sports Cardiology in Patients with Cardiovascular Diseases

Abstract: The prediction and prevention of sudden cardiac death is the philosopher’s stone of clinical cardiac electrophysiology. Sports can act as triggers of fatal arrhythmias and therefore it is essential to promptly frame the athlete at risk and to carefully evaluate the suitability for both competitive and recreational sports activity. A history of syncope or palpitations, the presence of premature ventricular complexes or more complex arrhythmias, a reduced left ventricular systolic function, or the presence of kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…High-intensity exercise impacts not only ACM progression but also other cardiovascular diseases considered that present with a high risk of SCD and fatal arrhythmias [ 108 ]. In studies of trained HCM mice, treadmill running demonstrated an overall improved response to the enhanced hemodynamic load, while forced swimming protocols revealed a concerning increase in fibrotic levels [ 109 ].…”
Section: The Deleterious Impact Of Exercise In Acm and Its Translatio...mentioning
confidence: 99%
“…High-intensity exercise impacts not only ACM progression but also other cardiovascular diseases considered that present with a high risk of SCD and fatal arrhythmias [ 108 ]. In studies of trained HCM mice, treadmill running demonstrated an overall improved response to the enhanced hemodynamic load, while forced swimming protocols revealed a concerning increase in fibrotic levels [ 109 ].…”
Section: The Deleterious Impact Of Exercise In Acm and Its Translatio...mentioning
confidence: 99%
“…Smith et al found that desmoplakin associated cardiomyopathy showed no correlation between exercise and risk of ventricular arrhythmias or LV/RV dysfunction, indicating that risk of arrhythmias may be specific to genotype ( 57 ). Risk and outcomes in ACM can change over time, therefore, it is imperative that ACM patients engaged in low or moderate activity be assessed yearly ( 12 , 58 ).…”
Section: Cardiomyopathies and Sports Participationmentioning
confidence: 99%
“…Moreover, the association between ARVC and sport activities is well‐known, as a significant percentage of SCDs concerning athletes have been attributed to this heart muscle disease. To lend more support, intense physical exercise can lead to disease progression 8 …”
Section: Introductionmentioning
confidence: 99%
“…To lend more support, intense physical exercise can lead to disease progression. 8 One of the most widely used tools for ARVC diagnosis are cardiovascular magnetic resonance (CMRI) and echocardiography. During the last decade, CMRI represents a useful medical tool for the efficient diagnosis of ARVC, permitting non-invasive morphological and functional evaluation accompanied by tissue characterization.…”
Section: Introductionmentioning
confidence: 99%